Effect of nonequilibrium hydrogen release in the ultrafine-grained Zr-1Nb alloy under the electron beam exposure; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Stepanova E. N. Ekaterina Nikolaevna; Grabovetskaya G. P.; Sypchenko V. S. Vladimir Sergeevich; Mishin I. P.; Kudiyarov V. N. Victor Nikolaevich; Melnikova T. N. Tamara Nikolaevna (2016, 2016)
Title screen